Survei Ketersediaan Fasilitas Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan Madrasah Ibtidaiyah di KecamatanKandangan Kabupaten Temanggung Tahun 2023 - Mukhamad Faiz Ridlo; Endang Sri Hanani; Cahyo Yuwono; Dwi Gansar Santi Wijayanti (Universitas Negeri Semarang, 2024)
The availability of inadequate facilities is very influential in the smooth learning process of physicaleducation sports and health. This research method is descriptive qualitative with survey researchdesign. Data collection techniques were carried out by interview, observation and documentation.The results showed (1) The availability of PJOK learning facilities is still inadequate, (2) The standard of PJOK learning facilities still does not meet the standards, (3) the feasibility of PJOK learning facilities is still mostly in the less feasible category. The conclusion in this study is that the survey of the availability of physical education learning facilities for sports and health of madrasah ibtidaiyah has not met the standards in facilitating PJOK learning activities, the suggestion in this study is that the foundation should improve the quality of PJOK learning facility standards